การวิจัยเชิงบูรณาการแบบองค์รวมเพื่อพัฒนาทักษะชีวิตของนักเรียนชั้นมัธยมศึกษาตอนปลาย - จินดา, ชวัลวิทย์; อเนกสุข, สมโภชน์ (Al-HIKMAH Journal, 2018)
This mixed method research aimed to 1) analyze confirmatory factors of life skills of high school students and investigate the perfect fit with the empirical data, 2) identify life-skill development activities for those students through holistically integrative research, and 3) study the outcomes of the life-skill development activities. Participants of this study were divided into two groups: the first group, designated for quantitative study, were 620 high-school students of The Secondary Educational Service Area 4, Saraburi Province. Instruments for this group were researcher-developed questionnaires. The second group, for qualitative study and the trial group, were 30 students whom purposively determined under the designated condition. The 60-item life skill assessment were used to collect data from this group. For data analysis, the statistic package program was used for analyzing basic statistics, while advanced statistic program was used for Confirmatory Factor Analysis, and content analysis was used to analyzed qualitative data. Results revealed; The second order CFA of high-school students’ life skill were congruent with the empirical data (c2 = 21.60, p = .6587, RMSEA = .00, and other factors met the set-criteria). Life-skill development of high school student through the holistically integrative research included eight activities as 1) Natural Music, 2) Crossing the Lines, 3) Reaching the Target, 4) What Do You do, 5) Emotional Flag Race, 6) No Anger, No Fear, 7) Problematic Communication, and 8) Finding Things with Eye Closed. The prominence of each life-skill development activity were 1) realization and actualization of self and others; students were happy and had fun, 2) creative decision making and problem solving; students were happy, had fun for being developed, for analyzing, making decision, and solving problem creatively, 3) emotion and stress management; students can show and manage their emotion in the activity including understand others’ emotion and feelings, and 4) making good relationship with others; students value the communication as it can make good relationship with others and good communication makes collaboration within the group.